A concept for removing the pollutants from air. (2022) - Deepak Singh, Desh; Mohan, Aditya; Walia, Ayush; Choudhary, Devansh; Khan, Kunwar Laiq Ahmad
Abstract: In this era of the 21st Century, in which several technologies are booming, and a lot of things are on the verge of a transformation from old man laboured technology into new Industry 4.0 based man less technology. However, these things which contribute to our comfortable life also result in a lot of wastage of resources. With the rise in the easiness of life in terms of transportation, there is an increase in usage of vehicles, manufacturing of goods and many such things. However, every action has its reaction, so this increase resulted further in terms different types of pollution such as Air Pollution, Water Pollution and Land Pollution. This wastage causes an Insufficient Atmosphere for living which resulted in several diseases in people of all ages. We are focussing mainly on the problem of air pollution and how we can reduce its impact on better living the individuals. Air pollution is one of the major causes of asthma, emphysema, and other respiratory diseases. Through air pollution, different types of hazardous substances are released into the air such as TRAP (Traffic Related Air Pollution), ozone gas, noxious gases (nitrous oxides and sulphur oxides), and particulate matter (PM) and so on. In this paper, a brief about the solution is provided, a concept or a product which will help remove pollutants from the air. The product will trap all the pollutants from the air, purify them and will produce clean and filtered air using various technologies like HEPA (High-Efficiency Particulate Air) Filters, Ultraviolet Lights and Activated Carbon.